Catechol-O-methyltransferase Val158-Met polymorphism and a response of hyperactive-impulsive symptoms to methylphenidate: A replication study from South Korea. (July 2014) - Park, Subin; Kim, Jae-Won; Kim, Bung-Nyun; Shin, Min-Sup; Yoo, Hee-Jeong; Cho, Soo-Churl
We investigated the association between the catechol-O-methyltransferase (COMT) Val 158 -Met (rs4680) genotype and both subjective and objective treatment responses to methylphenidate in Korean children with attention-deficit/hyperactivity disorder (ADHD). We enrolled 120 medication-naïve children with ADHD in an open-label, 8-week trial of methylphenidate. The participants were genotyped and evaluated using the Clinical Global Impression Scale and the ADHD Rating Scale-IV (ADHD-RS), and completed the Continuous Performance Test (CPT) before and after treatment. We found a significant association between the COMT Val/Val genotype and a good response, in terms of hyperactive-impulsive scores on the ADHD-RS (odds ratio (OR) = 2.61; p = 0.044) and response-time variability on the CPT (OR = 2.66; p = 0.028). The association of the COMT Val/Val genotype with a good response, in terms of response time variability, was significant in both the sub-sample of combined-type (OR = 3.45; p = 0.026) and sub-sample of inattentive-type (OR = 5.52; p = 0.029); but the association with a good response in terms of hyperactive-impulsive scores was not significant in sub-sample analyses. Although the reported nominally significant associations did not stay significant after correcting for multiple testing, our results support previous findings about the possible involvement of the COMT ( Val 158 -Met ) polymorphism in the treatment response to methylphenidate in children with ADHD.